Which regional inequality? the evolution of rural-urban and inland-coastal inequality in China from 1983 to 1995 - Kanbur, Ravi; Zhang, Xiaobo (Elsevier, 1999)
This paper develops a unified empirical framework for describing the relative contribution of rural–urban and inland–coastal inequality to overall regional inequality in China during the 1980's and 1990's. The framework assesses rural–urban and inland–coastal inequalities from the same data set, presents results for a sufficiently long time period to transcend short-term fluctuations, allows for differential price changes, and applies a consistent notion of the contribution to inequality using a decomposition analysis. While the contribution of rural–urban inequality is much higher than that of inland–coastal inequality in terms of levels, the trend is very different. The rural–urban contribution has not changed very much over time, but the inland–coastal contribution has increased by several fold. The paper ends by investigating the role of labor migration in this outcome. J. Comp. Econom., December 1999, 27(4), pp. 686–701. Department of Agricultural, Resource, and Managerial Economics, 309 Warren Hall, Cornell University, Ithaca, New York 14853; International Food Policy Research Institute, 2033 K Street, NW, Washington, DC 20006.